2013
DOI: 10.1098/rspb.2013.0849
|View full text |Cite
|
Sign up to set email alerts
|

Ecological variation in South American geophagine cichlids arose during an early burst of adaptive morphological and functional evolution

Abstract: Diversity and disparity are unequally distributed both phylogenetically and geographically. This uneven distribution may be owing to differences in diversification rates between clades resulting from processes such as adaptive radiation. We examined the rate and distribution of evolution in feeding biomechanics in the extremely diverse and continentally distributed South American geophagine cichlids. Evolutionary patterns in multivariate functional morphospace were examined using a phylomorphospace approach, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 53 publications
1
38
0
1
Order By: Relevance
“…Contrastingly, analysis of functionally explicit traits indicated that all South American lineages (i.e. additionally tribes Cichlini, Astronotini, Retroculini, Chaetobranchini, Cichlasomatini and some Heroini) contributed to a pattern of decreasing rates of functional evolution and finer partitioning of morphospace through time in the major clades of South American cichlids, alongside Geophagini [38]. Altogether, current evidence supports an early adaptive radiation of cichlids in South America, but support for an equivalent radiation in Central America remains ambiguous.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Contrastingly, analysis of functionally explicit traits indicated that all South American lineages (i.e. additionally tribes Cichlini, Astronotini, Retroculini, Chaetobranchini, Cichlasomatini and some Heroini) contributed to a pattern of decreasing rates of functional evolution and finer partitioning of morphospace through time in the major clades of South American cichlids, alongside Geophagini [38]. Altogether, current evidence supports an early adaptive radiation of cichlids in South America, but support for an equivalent radiation in Central America remains ambiguous.…”
Section: Discussionmentioning
confidence: 82%
“…This morphospace was derived from phylogenetic principal components analysis ( pPCA) of 10 morphological and biomechanical variables from 75 species representing all major lineages of Cichlinae [29], which were selected to represent as many tribes, genera and ecological variation as possible given specimen availability. These variables included two oral jaw muscle masses (1, adductor mandibulae and 2, sternohyoideus mass); 3, the mass of the lower pharyngeal jaw (fifth ceratobranchial); 4, maximum jaw protrusion distance; 5 -6, lower and upper jaw opening and closing mechanical advantages; 7, bite occlusion patterns (quadrate offset); 8-9 oral jaw and hyoid four bar lever transmission coefficients and 10, an index of suction feeding capability [29,38], and see the electronic supplementary material, table S1 for additional details. Data were collected from one to six specimens (housed at or on loan to the Royal Ontario Museum) per species (median ¼ 3; electronic supplementary material, table S6).…”
Section: Methods (A) Neotropical Cichlid Phylogenetics and Functionalmentioning
confidence: 99%
“…Recently, strong partitioning of ecologically meaningful body shape attributes [43] and trophic functional morphospace [46] was found in Cichlinae and it is likely that this ecological differentiation is correlated with patterns in BSFDs across the group. The distribution of body size in the GGD clade of Geophagini was found to be located between the two modes of the CAS clade, producing a third mode of body size that suggests partitioning of total body size morphospace.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, recent studies including T . preta have related the macroevolutionary diversification of the Crenicichla–Teleocichla clade to the emergence of adaptive peaks driven by innovative adaptive changes in swimming and feeding functional morphology (Arbour & López‐Fernández, , ; Astudillo‐Clavijo et al , ). The body and caudal peduncle of other species of Teleocichla from Rio Xingu tend to be more elongated, suggesting that there may be further variation in attributes of swimming performance within the genus.…”
Section: Discussionmentioning
confidence: 99%
“…preta is similar to that of many species in the clade, a common divergence of dentition and functional decoupling of the oral and pharyngeal sets of jaws widespread in cichlids (Hulsey et al , ). Arbour & López‐Fernández (, ) included T . preta in biomechanical analyses performed in the context of the Crenicichla–Teleocichla clade and of other Neotropical lineages of Cichlidae, respectively.…”
Section: Discussionmentioning
confidence: 99%